The Politics of Pension Reform under Ageing - Theo Leers; Lex Meijdam; Harrie A. A Verbon (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we address the question whether in case of population ageing a transition from an unfunded to a more funded pension scheme is politically feasible in a representative democracy. We consider two parties: a right-wing party which is willing to trade off intragenerational equity against efficiency gains in intergenerational redistribution, and a left-wing party which does not want to adjust the level of intragenerational distribution. We show that, in an economy with an exogenously given interest rate, only a thus defined right-wing government will propose a social-security reform. Moreover, we demonstrate that such a policy proposal may lead to electoral success if it entails an appropriate mix of distributional efficiency and equity.
Keywords: 330; Ageing; overlapping generations; pensions